A solder paste and a method of preparing and using the same
Patent Information
- Application Number
- CN202410084143.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-19
AI Technical Summary
[0004]然而采用焊料浆液涂胶过程中,由于现有的焊料浆液挥发速度过快,在涂胶过程中会较频繁出现断胶、少胶等现象,导致焊料浆液的涂覆不均匀,影响焊接良率
1.在磁控管生产的过程中,钍钨灯丝与钼端帽采用焊料钎焊时,常采用的是高频感应加热方式加温,在高频感应作用下,钼端帽由于集肤效应自身发热,然后将热传递给焊料使焊料融化,从而实现钍钨灯丝与钼端帽的钎焊固定;本申请通过对硅钼粉进行改性,聚酰胺可以与环氧树脂形成一定的网络结构,环氧树脂提供粘结性能,使焊料浆液可以更好涂布在钼端帽上,减少焊料浆液在涂胶的过程中出现断胶或少胶的情况,提高焊料浆液与磁控管阴极部的钼端帽的附着力,使钼端帽在焊接过程中不易出现鼓泡,进而提高焊接良率。
Smart Images

Figure BDA0004674164160000071 
Figure BDA0004674164160000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of solder paste, and in particular to a solder paste, its preparation method, and its application. Background Technology
[0002] The core of a magnetron is the cathode, which mainly consists of a thorium-tungsten filament, a molybdenum end cap, and a molybdenum support rod. During magnetron production, solder paste is applied to the molybdenum end cap, and the solder-coated end cap is then sintered to form the molybdenum end cap.
[0003] Applying solder slurry to the molybdenum end cap can provide a protective coating and promote the formation of the weld joint.
[0004] However, during the process of applying solder paste, the existing solder paste evaporates too quickly, which frequently leads to phenomena such as insufficient or no paste application, resulting in uneven solder paste coating and affecting the welding yield. Summary of the Invention
[0005] To improve welding yield, this application provides a solder slurry, its preparation method, and its application.
[0006] Firstly, this application provides a solder slurry using the following technical solution: A solder slurry comprising the following raw materials in parts by weight: 50-100 parts modified molybdenum silicon powder; 20-50 parts epoxy resin; 2-8 parts rheology modifier; 2-6 parts diluent; and 5-25 parts solvent; wherein the modified molybdenum silicon powder is made from the following raw materials: molybdenum silicon powder, silane coupling agent, and polyamide.
[0007] By adopting the above technical solution, in the process of magnetron production, when the thorium-tungsten filament and the molybdenum end cap are brazed with solder, high-frequency induction heating is often used. Under the action of high-frequency induction, the molybdenum end cap heats up due to the skin effect, and then transfers the heat to the solder to melt the solder, thereby achieving the brazing and fixing of the thorium-tungsten filament and the molybdenum end cap. This application modifies the silicon molybdenum powder, and the polyamide can form a certain network structure with the epoxy resin. The epoxy resin provides bonding properties, which allows the solder slurry to be better coated on the molybdenum end cap, reducing the occurrence of glue breakage or insufficient glue during the coating process, improving the adhesion between the solder slurry and the molybdenum end cap of the magnetron cathode, making the molybdenum end cap less prone to blistering during the welding process, and thus improving the welding yield.
[0008] Preferably, the solder slurry further includes the following raw materials in parts by weight: 10-20 parts of ethyl cellulose; 2-4 parts of defoamer.
[0009] By adopting the above technical solution, ethyl cellulose itself has high physicochemical properties, good high-temperature performance, corrosion resistance and plasticity, which can meet various welding requirements. Solder made with ethyl cellulose has good stability and durability during use, thereby maintaining welding quality and welding strength. In the production of magnetrons, it improves the adhesion stability of solder slurry to molybdenum end caps. Defoamer can also eliminate air bubbles in solder slurry, which is beneficial to improving the bonding strength between solder slurry and molybdenum end caps.
[0010] Preferably, the modified silicon molybdenum powder is prepared by mixing 10-30 parts by weight of silicon molybdenum powder, 30-50 parts by weight of polyamide, 10-20 parts by weight of silane coupling agent and 40-80 parts by weight of ethanol, followed by ultrasonic dispersion, centrifugation and drying to obtain the silicon molybdenum powder.
[0011] By adopting the above technical solution, this application improves the interfacial bonding force between silicon molybdenum powder and epoxy resin through silane coupling agent modification, thereby improving mechanical properties, increasing the elongation of silicon molybdenum powder, improving the coatability of solder slurry, and facilitating the integration of solder and molybdenum end cap; at the same time, polyamide has excellent mechanical properties, and after being uniformly dispersed in silicon molybdenum powder, it forms a certain network structure with epoxy resin, effectively improving the stability of solder slurry and playing a role in thickening and stabilizing.
[0012] Preferably, the weight ratio of the molybdenum silicate powder, polyamide, and silane coupling agent is 1:(2.15-2.4):(0.6-0.75).
[0013] By adopting the above technical solution, when the silicon molybdenum powder, polyamide, and silane coupling agent are in a specific weight ratio, the three work together. Polyamide can improve the interaction between silicon molybdenum powder and silane coupling agent, and has a thickening effect on solder slurry. By forming a through network in the components, the components of the solder slurry are evenly dispersed, the fluidity of the solder slurry is improved, and a certain thickening and stabilizing effect is achieved.
[0014] Preferably, the modified epoxy resin is prepared by: heating and mixing 20-40 parts by weight of polymethylhydrosiloxane, 24-48 parts by weight of allyl alcohol polyoxyalkylene ether and 0.5-1 parts by weight of chloroplatinic acid, and distilling to obtain a pre-prepared product; stirring and dispersing the pre-prepared product with 40-60 parts by weight of epoxy resin, 10-20 parts by weight of fumed silica and 25-45 parts by weight of xylene, and then adding 2-4 parts by weight of γ-aminopropyltriethoxysilane and 10-20 parts by weight of rosin to obtain the modified epoxy resin.
[0015] By adopting the above technical solution, this application modifies the epoxy resin. Polymethylhydrosiloxane is incompatible with epoxy resin. After adding polymethylhydrosiloxane for physical blending and curing, polymethylhydrosiloxane will slowly precipitate on the surface of epoxy resin, giving the solder slurry good adhesion. This makes it less likely for blistering to occur when the solder slurry is welded to the molybdenum end cap of the magnetron cathode plate, thus improving the welding yield.
[0016] Preferably, the weight ratio of the polymethylhydrosiloxane, allyl alcohol polyoxyalkylene ether and epoxy resin is 1:(0.9-1.1):(1.6-1.9).
[0017] By adopting the above technical solution, when polymethylhydrosiloxane, allyl alcohol polyoxyalkylene ether and epoxy resin are mixed in a specific weight ratio, the three components work together to improve the bonding performance of epoxy resin, thereby making it less likely for blistering to occur when the solder slurry is welded to the molybdenum end cap of the magnetron cathode plate, thus improving the welding yield.
[0018] Preferably, the particle size range of the silicon molybdenum powder is 10-20 μm.
[0019] By adopting the above technical solution, controlling the particle size range of silicon molybdenum powder can make the silicon molybdenum powder uniformly dispersed in other components, thereby improving the welding effect and further reducing the welding defect rate.
[0020] Preferably, the weight ratio of the modified molybdenum silica powder, modified epoxy resin and ethyl cellulose is (8-9):(2.7-3.2):1.
[0021] By adopting the above technical solution, when modified silicon molybdenum powder, modified epoxy resin and ethyl cellulose are in a specific weight ratio, ethyl cellulose provides good stability during the welding process, which helps to improve welding quality and welding strength. The magnetron, together with the modified silicon molybdenum powder and modified epoxy resin, further improves the fluidity and stability of the solder slurry.
[0022] Secondly, the method for preparing solder slurry provided in this application adopts the following technical solution: A method for preparing a solder slurry includes the following steps: mixing modified molybdenum silicon powder, epoxy resin, rheology modifier, diluent and solvent evenly according to the specified ratio to obtain the solder slurry.
[0023] By adopting the above technical solution, solder slurry with good fluidity and stability can be easily and conveniently prepared.
[0024] Thirdly, the application of the solder slurry provided in this application adopts the following technical solution: An application of a solder slurry for coating a molybdenum end cap and sintering the molybdenum end cap to assemble a magnetron cathode.
[0025] By adopting the above technical solution, the molybdenum end cap in the cathode section of the magnetron can be welded more firmly.
[0026] In summary, this application has the following beneficial technical effects: 1. In the production process of magnetrons, when thorium-tungsten filaments and molybdenum end caps are brazed with solder, high-frequency induction heating is commonly used. Under the action of high-frequency induction, the molybdenum end cap heats up due to the skin effect, and then transfers the heat to the solder to melt it, thereby achieving the brazing and fixing of the thorium-tungsten filament and the molybdenum end cap. This application modifies the silicon molybdenum powder, allowing polyamide to form a certain network structure with epoxy resin. The epoxy resin provides bonding properties, enabling the solder slurry to be better coated on the molybdenum end cap, reducing the occurrence of solder slurry breakage or insufficient coating during the coating process, improving the adhesion between the solder slurry and the molybdenum end cap at the cathode of the magnetron, making the molybdenum end cap less prone to blistering during the welding process, and thus improving the welding yield.
[0027] 2. This application improves the interfacial bonding force between silicon molybdenum powder and epoxy resin by modifying with silane coupling agents, thereby enhancing mechanical properties, increasing the elongation of silicon molybdenum powder, improving the coatability of solder slurry, and facilitating the integration of solder and molybdenum end caps; at the same time, polyamide has excellent mechanical properties, and after being uniformly dispersed in silicon molybdenum powder, it forms a certain network structure with epoxy resin, effectively improving the stability of solder slurry and playing a thickening and stabilizing role. Detailed Implementation
[0028] The present application will be further described in detail below with reference to embodiments and comparative examples.
[0029] Example 1 A method for preparing solder slurry: 50g of modified molybdenum silicon powder, 20g of epoxy resin, and 5g of acetone solvent are added to a stirrer and stirred for 10 minutes at 500 rpm. Then, 2g of polyethylene wax rheology modifier and 2g of ethylene glycol diglycidyl ether diluent are added and mixed evenly for 20 minutes at 1200 rpm to obtain the solder slurry. The epoxy resin was purchased from Jinan Jibin Chemical Co., Ltd., epoxy resin E51, with an epoxy value of 0.52 mol / 100g and a density of 1.2 g / cm³. 3 For polyethylene wax, we selected SCG polyethylene wax LP0020P from Thailand; for ethylene glycol diglycidyl ether diluent, we selected LA584156 from Shandong Li'ang New Material Technology Co., Ltd.
[0030] The modified silicon-molybdenum powder was prepared as follows: 10g of silicon-molybdenum powder, 30g of polyamide, 10g of silane coupling agent KH550, and 40g of ethanol were added to a stirrer and mixed for 10 minutes, followed by ultrasonic dispersion for 4 hours. The mixture was then centrifuged and transferred to an oven to dry at 100℃ for 2 hours to obtain the modified silicon-molybdenum powder. The weight ratio of Si to Mo in the silicon-molybdenum powder was 1:9, and the polyamide was selected from BASF A3K (Germany).
[0031] Example 2 A method for preparing solder slurry: 100g of modified molybdenum silicon powder, 50g of epoxy resin, and 25g of acetone solvent are added to a stirrer and stirred for 10 minutes at 500 rpm. Then, 8g of rheology modifier and 6g of ethylene glycol diglycidyl ether diluent are added and mixed evenly for 20 minutes at 1200 rpm to obtain the solder slurry. The epoxy resin was purchased from Jinan Jibin Chemical Co., Ltd., epoxy resin E51, with an epoxy value of 0.52 mol / 100g and a density of 1.2 g / cm³. 3 For polyethylene wax, we selected SCG polyethylene wax LP0020P from Thailand; for ethylene glycol diglycidyl ether diluent, we selected LA584156 from Shandong Li'ang New Material Technology Co., Ltd.
[0032] The modified silicon-molybdenum powder was prepared as follows: 10g of silicon-molybdenum powder, 30g of polyamide, 10g of silane coupling agent KH550, and 40g of ethanol were added to a stirrer and mixed for 10 minutes, followed by ultrasonic dispersion for 4 hours. The mixture was then centrifuged and transferred to an oven to dry at 100℃ for 2 hours to obtain the modified silicon-molybdenum powder. The weight ratio of Si to Mo in the silicon-molybdenum powder was 1:9, and the polyamide was selected from BASF A3K (Germany).
[0033] Example 3 A method for preparing solder slurry: 75g of modified molybdenum silicon powder, 35g of epoxy resin, and 15g of acetone solvent are added to a stirrer and stirred for 10 minutes at 500 rpm. Then, 5g of rheology modifier and 4g of ethylene glycol diglycidyl ether diluent are added and mixed evenly for 20 minutes at 1200 rpm to obtain the solder slurry. The epoxy resin was purchased from Jinan Jibin Chemical Co., Ltd., epoxy resin E51, with an epoxy value of 0.52 mol / 100g and a density of 1.2 g / cm³. 3 For polyethylene wax, we selected SCG polyethylene wax LP0020P from Thailand; for ethylene glycol diglycidyl ether diluent, we selected LA584156 from Shandong Li'ang New Material Technology Co., Ltd.
[0034] The modified silicon-molybdenum powder was prepared as follows: 10g of silicon-molybdenum powder, 30g of polyamide, 10g of silane coupling agent KH550, and 40g of ethanol were added to a stirrer and mixed for 10 minutes, followed by ultrasonic dispersion for 4 hours. The mixture was then centrifuged and transferred to an oven to dry at 100℃ for 2 hours to obtain the modified silicon-molybdenum powder. The weight ratio of Si to Mo in the silicon-molybdenum powder was 1:9, and the polyamide was selected from BASF A3K (Germany).
[0035] Example 4 A method for preparing solder slurry differs from Example 3 in that the modified silicon molybdenum powder is prepared as follows: 30g silicon molybdenum powder, 50g polyamide, 20g silane coupling agent KH550 and 80g ethanol are added to a stirrer and mixed for 10 minutes, then ultrasonically dispersed for 4 hours, centrifuged, transferred to an oven and dried at 100°C for 2 hours to obtain modified silicon molybdenum powder.
[0036] Example 5 A method for preparing solder slurry differs from Example 3 in that, in the process of preparing modified silicon molybdenum powder, the amount of silicon molybdenum powder added is 20g, the amount of polyamide added is 43g, and the amount of silane coupling agent KH550 added is 12g.
[0037] Example 6 A method for preparing solder slurry differs from Example 3 in that, in the process of preparing modified silicon molybdenum powder, the amount of silicon molybdenum powder added is 20g, the amount of polyamide added is 48g, and the amount of silane coupling agent KH550 added is 15g.
[0038] Example 7 A method for preparing a solder slurry differs from Example 3 in that an equal amount of epoxy resin is replaced with modified epoxy resin. The modified epoxy resin is prepared as follows: 20g of polymethylhydrosiloxane, 24g of allyl alcohol polyoxyalkylene ether, and 0.5g of chloroplatinic acid are heated to 100°C under nitrogen protection and reacted for 8 hours. After distillation, a pre-prepared product is obtained. The pre-prepared product is then mixed with 40g of epoxy resin, 10g of fumed silica, and 25g of xylene at a stirring speed of 400r / min for 90 minutes. Then, 2g of γ-aminopropyltriethoxysilane and 10g of rosin are added, and the mixture is stirred at a speed of 200r / min for 60 minutes to obtain the modified epoxy resin. The allyl alcohol polyoxyalkylene ether has a hydroxyl value of 50mgKOH / g and an acid value of 0.5mgKOH / g. The polymethylhydrosiloxane used is Jixin Yibang, model number 63148-57-2.
[0039] Example 8 A method for preparing a solder slurry differs from Example 3 in that an equal amount of epoxy resin is replaced with modified epoxy resin. The modified epoxy resin is prepared as follows: 40g of polymethylhydrosiloxane, 48g of allyl alcohol polyoxyalkylene ether, and 1g of chloroplatinic acid are heated to 100°C under nitrogen protection and reacted for 8 hours. After distillation, a pre-prepared product is obtained. The pre-prepared product is then mixed with 60g of epoxy resin, 20g of fumed silica, and 45g of xylene at a stirring speed of 400r / min for 90 minutes. Then, 4g of γ-aminopropyltriethoxysilane and 20g of rosin are added, and the mixture is stirred at a speed of 200r / min for 60 minutes to obtain the modified epoxy resin. The allyl alcohol polyoxyalkylene ether has a hydroxyl value of 50mgKOH / g and an acid value of 0.5mgKOH / g. The polymethylhydrosiloxane used is Jixin Yibang, model number 63148-57-2.
[0040] Example 9 A method for preparing solder slurry differs from Example 8 in that, in the process of preparing modified epoxy resin, the amount of polymethylhydrosiloxane added is 30g, the amount of allyl alcohol polyoxyalkylene ether added is 27g, and the amount of epoxy resin added is 48g.
[0041] Example 10 A method for preparing solder slurry differs from Example 8 in that, in the process of preparing modified epoxy resin, the amount of polymethylhydrosiloxane added is 30g, the amount of allyl alcohol polyoxyalkylene ether added is 33g, and the amount of epoxy resin added is 57g.
[0042] Example 11 A method for preparing solder slurry differs from Example 10 in that 75g of modified molybdenum silicon powder, 35g of modified epoxy resin, 10g of ethyl cellulose, 2g of polyvinyl alcohol defoamer, and 15g of solvent are added to a stirrer and stirred for 10 minutes at 500 rpm. Then, 5g of rheology modifier and 4g of diluent are added and mixed evenly for 20 minutes at 1200 rpm to obtain the solder slurry. The polyvinyl alcohol was purchased from Jiangsu Carver New Material Technology Co., Ltd., and its viscosity was 50 MPa·s.
[0043] Example 12 A method for preparing solder slurry, differing from Example 10, involves adding 75g of modified molybdenum silicon powder, 35g of modified epoxy resin, 20g of ethyl cellulose, 4g of defoamer, and 15g of solvent to a stirrer and stirring at 500 rpm for 10 minutes. Then, 5g of rheology modifier and 4g of diluent are added, and the mixture is stirred evenly at 1200 rpm for 20 minutes to obtain the solder slurry. Polyvinyl alcohol was purchased from Jiangsu Carver New Material Technology Co., Ltd., with a viscosity of 50 MPa·s.
[0044] Example 13 A method for preparing solder slurry differs from Example 12 in that the amount of modified molybdenum silicon powder is 80g, the amount of modified epoxy resin is 27g, and the amount of ethyl cellulose is 10g.
[0045] Example 14 A method for preparing solder slurry differs from Example 12 in that the amount of modified molybdenum silicon powder is 90g, the amount of modified epoxy resin is 32g, and the amount of ethyl cellulose is 10g.
[0046] Comparative Example Comparative Example 1 A method for preparing solder slurry differs from Example 3 in that modified silicon molybdenum powder is replaced with silicon molybdenum powder in equal amounts.
[0047] Comparative Example 2 A method for preparing solder slurry, which differs from Example 10 in that ethyl cellulose is replaced with an equal amount of hydroxypropyl methyl cellulose.
[0048] Comparative Example 3 A method for preparing solder slurry, which differs from Example 3 in that an equal amount of epoxy resin is replaced with ethylene-vinyl acetate copolymer.
[0049] Comparative Example 4 A method for preparing solder slurry differs from Example 14 in that the amount of modified molybdenum silicon powder added is 75g and the amount of modified epoxy resin added is 70g.
[0050] Application examples Application Example 1-14 An application of a solder slurry involves coating the solder slurry prepared in Examples 1-14 onto a molybdenum end cap, sintering it at 700°C for 4 hours, and then sintering it at 1500°C for 2 hours to obtain a magnetron.
[0051] Compare and contrast examples 1-4 An application of solder slurry involves coating the solder slurry prepared in Comparative Examples 1-4 onto a molybdenum end cap, sintering it at 700°C for 4 hours, and then sintering it at 1500°C for 2 hours to obtain a magnetron.
[0052] Performance testing: Flowability: The solder slurries prepared in Examples 1-14 and Comparative Examples 1-4 were stored at room temperature for 1 month. The flowability was judged based on the flowability of the solder slurries: Grade 1 flows at room temperature; Grade 2 does not flow at room temperature, but is soft and easy to stir; Grade 3 is solid at room temperature and is difficult to stir.
[0053] Stability: The solder slurries prepared in Examples 1-14 and Comparative Examples 1-4 were stored at 40°C for 7 days. The difference in viscosity before and after storage was measured using a PCU-205 automatic viscometer. The smaller the viscosity change, the better the stability over time.
[0054] Welding yield: 1000 magnetron cathode assemblies were randomly selected from Application Examples 1-14 and Comparative Application Examples 1-4. The molybdenum end caps of the magnetron cathode assemblies were checked for bubbling issues. If even one molybdenum end cap in a magnetron cathode assembly showed a bubbling issue, it was included in the molybdenum end cap bubbling category. The average bubbling rate of molybdenum end caps for magnetron cathode assemblies obtained from different application examples and comparative application examples is recorded in the table below. Average bubbling rate of molybdenum end caps = Average number of molybdenum end cap bubbles / 1000 * 100.
[0055] Based on the data comparison of Application Examples 1-3 and Comparative Application Examples 1-4, it can be seen that by modifying the silicon molybdenum powder, the polyamide can form a certain network structure with the epoxy resin. The epoxy resin provides bonding properties, allowing the solder slurry to be better coated on the molybdenum end cap, reducing the occurrence of solder slurry breakage or insufficient coating during the coating process, improving the adhesion between the solder slurry and the molybdenum end cap of the magnetron cathode, making the molybdenum end cap less prone to bubbling during the welding process, thereby improving the welding yield.
[0056] Based on the data comparison of application examples 3-6, it can be seen that when the silicon molybdenum powder, polyamide, and silane coupling agent are in a specific weight ratio, the three work together. Polyamide can improve the interaction between silicon molybdenum powder and silane coupling agent, and has a thickening effect on solder slurry. By forming a through network in the components, polyamide can make the components of solder slurry evenly dispersed, improve the fluidity of solder slurry, and play a certain role in thickening and stabilizing.
[0057] Based on the data comparison of application examples 6-8, it can be seen that by modifying the epoxy resin, polymethylhydrosiloxane is incompatible with epoxy resin. After adding polymethylhydrosiloxane for physical blending and curing, polymethylhydrosiloxane will slowly precipitate on the surface of epoxy resin, giving the solder slurry good adhesion. This makes it less likely for blistering to occur when the solder slurry is welded to the molybdenum end cap of the magnetron cathode plate, thus improving the welding yield.
[0058] Based on the data comparison of application examples 8-10, it can be seen that when polymethylhydrosiloxane, allyl alcohol polyoxyalkylene ether, and epoxy resin are in a specific weight ratio, the combination of the three is beneficial to improving the bonding performance of epoxy resin, thereby making it less likely for blistering to occur when the solder slurry is welded to the molybdenum end cap of the magnetron cathode plate, thus improving the welding yield.
[0059] Based on the data comparison of application examples 10-12, it can be seen that ethyl cellulose itself has high physicochemical properties, good high-temperature performance, corrosion resistance and plasticity, which can meet various welding requirements. Solder made with ethyl cellulose has good stability and durability during use, thereby maintaining welding quality and welding strength. In the production of magnetrons, it improves the adhesion stability of solder slurry to molybdenum end caps. Defoamer can also eliminate air bubbles in solder slurry, which is beneficial to improving the adhesion strength between solder slurry and molybdenum end caps.
[0060] According to the data comparison of application examples 12-14, when modified molybdenum silicon powder, modified epoxy resin and ethyl cellulose are in a specific weight ratio, ethyl cellulose provides good stability during the welding process, which helps to improve the welding quality and welding strength. The magnetron, together with the modified molybdenum silicon powder and modified epoxy resin, further improves the fluidity and stability of the solder slurry.
[0061] The specific embodiments are merely explanations of this application and are not intended to limit it. Those skilled in the art can make modifications to these embodiments without contributing any inventive step after reading this specification, but such modifications are protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. A solder slurry, characterized in that: The raw materials include the following parts by weight: 50-100 parts of modified molybdenum silica powder; 20-50 parts of epoxy resin; 2-8 parts of rheology modifier; 2-6 parts of diluent; and 5-25 parts of solvent. The modified molybdenum silica powder is made from the following raw materials: molybdenum silica powder, silane coupling agent, and polyamide. The modified silicon molybdenum powder is prepared by mixing 10-30 parts by weight of silicon molybdenum powder, 30-50 parts by weight of polyamide, 10-20 parts by weight of silane coupling agent and 40-80 parts by weight of ethanol, followed by ultrasonic dispersion, centrifugation and drying to obtain the modified silicon molybdenum powder. The weight ratio of the molybdenum silicate powder, polyamide, and silane coupling agent is 1:(2.15-2.4):(0.6-0.75).
2. The solder slurry according to claim 1, characterized in that: The solder slurry also includes the following raw materials in parts by weight: 10-20 parts of ethyl cellulose; 2-4 parts of defoamer.
3. The solder slurry according to claim 1, characterized in that: The epoxy resin is a modified epoxy resin. The preparation method of the modified epoxy resin is as follows: 20-40 parts by weight of polymethylhydrosiloxane, 24-48 parts by weight of allyl alcohol polyoxyalkylene ether and 0.5-1 parts by weight of chloroplatinic acid are heated and mixed to react, and then distilled to obtain a pre-prepared product; the pre-prepared product is stirred and dispersed with 40-60 parts by weight of epoxy resin, 10-20 parts by weight of fumed silica and 25-45 parts by weight of xylene, and then 2-4 parts by weight of γ-aminopropyltriethoxysilane and 10-20 parts by weight of rosin are added and stirred to obtain the modified epoxy resin.
4. The solder slurry according to claim 3, characterized in that: The weight ratio of the polymethylhydrosiloxane, allyl alcohol polyoxyalkylene ether and epoxy resin is 1:(0.9-1.1):(1.6-1.9).
5. The solder slurry according to claim 1, characterized in that: The particle size range of the silicon molybdenum powder is 10-20 μm.
6. The solder slurry according to claim 3, characterized in that: The weight ratio of the modified molybdenum silica powder, modified epoxy resin and ethyl cellulose is (8-9):(2.7-3.2):
1.
7. A method for preparing solder slurry, characterized in that: The method for preparing the solder slurry according to any one of claims 1-6 includes the following steps: mixing modified molybdenum silicon powder, epoxy resin, rheology modifier, diluent and solvent uniformly according to the formula to obtain the solder slurry.
8. An application of a solder slurry, characterized in that: The magnetron cathode portion is prepared by coating a molybdenum end cap with the solder slurry described in any one of claims 1-6 and sintering the molybdenum end cap.
Citation Information
Patent Citations
Preparation method of solder for magnetron cathode assembly
CN111098061A
High-stability environment-friendly soldering paste and preparation method thereof
CN112975200A
Solder Paste and Electronic Device Using Same
US20070277909A1
